A way forward: Policy-driven transformation - Breisinger, Clemens; Keenan, Michael; Mbuthia, Juneweenex (International Food Policy Research Institute, 2023)
This book has adopted a food systems framework as a new way of conceptualizing and designing food policies and research. Looking beyond agriculture and value chains makes it possible not only to turn food systems into a driver of economic transformation but also to better include health, productivity, resilience, inclusivity, and sustainability as integral parts of system transformation. Such a fresh approach is urgently needed in light of limited development progress over the past years in Kenya and other countries. The share of manufacturing—traditionally a driver of economic transformation—in total output remains low; maize yields have been stagnating for the past 20 years; and poverty and food insecurity are on the rise again (Nafula et al. 2020; FAOSTAT 2022). In addition to structural challenges, growing challenges and vulnerabilities such as the threat of pandemics, commodity price crises, climate change, and conflicts, call for a new development and food policy paradigm (Breisinger et al. 2022; UNICEF 2022). At the same time, such a fresh approach can also help in harnessing the new opportunities that come with digitalization and with (policy) lessons from other countries that can be adapted to the Kenyan context.